TRAINING ON THE PREPARATION OF BUSINESS MODEL CANVAS FOR HIGH SCHOOL STUDENTS AT THE EQUIVALENT TO IMPROVE INNOVATION AND ENTREPRENEURIAL SKILLS IN THE DIGITAL ERA IN THE CITY OF LHOKSEUMAWE - Muhammad Hafizh; Mutia Rahmah; Noviami Trisniarti; Nabila novianita; Safuani Marsya (RADJA PUBLIKA, 2024)
This community service program aims to provide training on the preparation of Business Model Canvas (BMC) to high school students in Lhokseumawe City. This training is important because before it is held, students do not understand the main components of BMC, including the appropriate target market. The main problem faced by students is the inability to identify the type of business and target market, so they have difficulty determining the right product or service. This training can improve students' understanding of various components of business, create a clear vision, and help them explore opportunities and challenges that exist in society. BMC training also encourages innovation and creative thinking, and helps to improve business performance on a regular basis. The implementation method used is through direct training with a focus on practical and applicative understanding of BMC. The results of this training are in the form of improving students' entrepreneurial skills, the ability to design product marketing strategies, adapting to market changes, and increasing business competitiveness. The resulting impact is that students are better prepared to face the business world in the future, and are able to develop a sustainable business by understanding and applying the Business Model Canvas design. The outcomes of this program include students' practical and strategic understanding of the preparation of innovative Canvas business models.